Comprehensive Outcomes Evaluation After Percutaneous Coronary Intervention in Stable Ischemic Heart Disease and Acute Coronary Syndrome for Short- Versus Standard-Term Dual Antiplatelet Therapy: A Systematic Review and Meta-analysis of Randomized Control Trials. Issue 5 (November 2020) - Bhattarai, Mukul; Ibrahim, Abdisamad M.; Salih, Mohsin; Tandan, Nitin; Al-Akchar, Mohammad; Ayan, Mohamed; Kulkarni, Abhishek; Hafiz, Abdul M.
Abstract : Abstract: Newer generation drug eluting stents (DES) and pharmacotherapy have decreased thrombotic events post-percutaneous coronary intervention (PCI). There is lack of wide-ranging safety and efficacy evaluation in both stable ischemic heart disease and acute coronary syndrome in short-term (3–6 months) versus Standard-term (12 months) dual antiplatelet therapy (DAPT). We searched electronic databases using specific terms to identify randomized control trials comparing different durations of DAPT after PCI with DES. The outcomes of interest included all-cause mortality, myocardial infarction, stent thrombosis, major bleeding, target lesion and vessel revascularization, and stroke at follow-up duration ≥12 months post index PCI. Studies that compared DAPT <3 months or DAPT ≥12 months were excluded. Thirteen randomized control trials (n = 31, 831) were included; 8401 patients received DAPT for 3 months and 7482 patients received DAPT in the 6 months group. Major bleeding rate was lower in the short-term (3–6 months) versus Standard-term (12 months) group (risk ratio 0.66; 95% confidence interval, 0.52–0.84, P < 0.05). Repeat revascularization rate was higher in the short-term (3–6 months) versus Standard-term (12 months) (risk ratio 1.17; 95% confidence interval, 1.01–1.36, P < 0.05) of DAPT duration after PCI with DES. No difference in other outcomes were observed when comparing short versus standard duration of DAPT in both stable ischemic heart disease and acute coronary syndrome.